Experimental Evaluation of the Seismic Response of Skewed Bridges with Emphasis on Poundings between Girder and Abutments - Ziqi Yang; Chern Kun; Nawawi Chouw (Shock and Vibration)
Observations from past earthquake events indicate that skewed bridges are seismically vulnerable due to induced horizontal in-plane rotations of the girder. To date, however, very limited experimental research has been done on the pounding behaviour of skewed bridges. In this study, shake table tests were performed on a single-frame bridge model with adjacent abutments subjected to uniform ground excitations. Bridges with different skew angles, i.e., 0°, 30°, and 45°, were considered. The pounding behaviour was observed using a pair of pounding and measuring heads. The results reveal that poundings could indeed influence the responses of skewed bridges in the longitudinal and transverse directions differently and thus affect the development of the girder rotations. Ignoring pounding effects, the 30° skewed bridges could experience more girder rotations than the 45° skewed bridges. With pounding, the bridges with a large skew angle could suffer more opening girder displacements than straight bridges.